Methods of Purification and Application Procedures of Alpha1 Antitrypsin: A Long-Lasting History - Simona Viglio (Molecules, 2020)
The aim of the present report is to review the literature addressing the methods developed for the purification of alpha1-antitrypsin (AAT) from the 1950s to the present. AAT is a glycoprotein whose main function is to protect tissues from human neutrophil elastase (HNE) and other proteases released by neutrophils during an inflammatory state. The lack of this inhibitor in human serum is responsible for the onset of alpha1-antitrypsin deficiency (AATD), which is a severe genetic disorder that affects lungs in adults and for which there is currently no cure. Being used, under special circumstances, as a medical treatment of AATD in the so-called “replacement” therapy (consisting in the intravenous infusion of the missing protein), AAT is a molecule with a lot of therapeutic importance. For this reason, interest in AAT purification from human plasma or its production in a recombinant version has grown considerably in recent years. This article retraces all technological advances that allowed the manufacturers to move from a few micrograms of partially purified AAT to several grams of highly purified protein. Moreover, the chronic augmentation and maintenance therapy in individuals with emphysema due to congenital AAT deficiency (current applications in the clinical setting) is also presented.